2014
DOI: 10.1002/ana.24219
|View full text |Cite
|
Sign up to set email alerts
|

PLXNA4 is associated with Alzheimer disease and modulates tau phosphorylation

Abstract: Objective Much of the genetic basis for Alzheimer disease (AD) is unexplained. We sought to identify novel AD loci using a unique family-based approach that can detect robust associations with infrequent variants (minor allele frequency <0.10). Methods We conducted a genome-wide association study in the Framingham Heart Study (FHS) (discovery) and NIA-LOAD (replication) family-based cohorts using an approach that accounts for family structure and calculates a risk score for AD as the outcome. Links between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 48 publications
1
60
1
Order By: Relevance
“…According to the outcome of our case-control research, evidence shows the minor T allele play no effect the LOAD risk in the group of APOE ε4 carriers. This outcome is in different with Gyungah Jun's study in Japanese published in 2014 (22). The MAF of rs13232207 in healthy controls in our research was 0.229.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…According to the outcome of our case-control research, evidence shows the minor T allele play no effect the LOAD risk in the group of APOE ε4 carriers. This outcome is in different with Gyungah Jun's study in Japanese published in 2014 (22). The MAF of rs13232207 in healthy controls in our research was 0.229.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, sample sizes in different investigation, population-specific differences as well as gene to gene or gene to environment interactions may also contribute towards this discrepancy in different ethnicity. PLXNA4 was first proposed to be associated with precise positioning of OPCs in developing cerebral cortex in 2012 (21), Jun's study then suggested that PLXNA4 do not influence APP processing or Aβ production but its isoform differentially affect Tau protein phosphorylation (22). Through the Tau phosphorylation, disrupted semaphorinplexin signaling is involved in AD pathogenesis, leading to neurofibrillary tangle formation and neuronal death (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A novel method of incorporating the entire family structure to reduce bias was used in a family-based GWAS, which generated strong evidence for a novel association of PLXNA4 with AD [62]. The first genome-wide epistasis study for AD was performed using GWAS data with a protocol for exhaustive epistasis screening, which revealed an AD-associated interacting SNP-pair of the KHDRBS2 and the CRYL1 genes [63].…”
Section: Other Forms Of Gwass In Admentioning
confidence: 99%